Acute Fasting-Induced Repression of the Hypothalamic-Pituitary-Gonadal Axis is Reversed by RF-9 Administration in the Adult Male Macaque - Batool, A.; Naz, R.; Wazir, M.; Azam, A.; Ullah, R.; Wahab, F.; Shahab, M. (Hormone and Metabolic Research, 2014)
Recently, hypothalamic RFRP-3 (a mammalian ortholog of avian GnIH) signaling has been proposed as an important negative modulator of the reproductive axis. The current study examined whether repression of reproductive hormonal expression during short-term fasting conditions in higher-order primate is influenced by altered RFRP-3 signaling. Eight intact postpubertal male macaques (Macaca mulatta) were administered a single intravenous bolus of RF-9 (n=4), a potent and putative RFRP-3 receptor antagonist, or vehicle (n=4) following a 48-h fasting condition. Intermittent blood samples were collected every 30 min during the 4-h post-bolus period, and blood glucose, plasma cortisol, and testosterone concentrations were measured. Relative to fed conditions, fasting reduced glucose and testosterone levels (p<0.005) and increased cortisol levels (p<0.05). Relative to baseline, mean testosterone levels were elevated 150 min after RF-9 (p<0.05) but not vehicle administration. In addition, elevated mean plasma testosterone levels following RF-9 administration were equivalent to levels observed in normal fed monkeys. These results suggest an important role for RFRP-3 signaling in conveying metabolic state information to the reproductive axis in higher primates.
Keywords: RFRP-3; RF-9; testosterone; GnIH; monkey; fasting